Kualitas Semen Beku Sapi Bali pada Penyimpanan Suhu Kamar - Hoesni, Fachroerozi; Adisetiawan, R.; Farizal, Farizal (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to determine the survival rate of frozen semen from Bali cattle on a liquid nitrogen surface. The research design used was a Completely Randomized Design (CRD) consisting of 5 treatments and 5 replications. The lifting and immersion treatment of frozen cement is based on the distance of the frozen cement from the liquid nitrogen surface at P0 (Control), P1 (5 cm for 5 minutes), P2 (10 cm for 5 minutes), P3 (15 cm for 5 minutes), P4 (20 cm for 5 minutes), and P4 (25 cm for 5 minutes). The variables observed were motility, survival percentage and abnormalities. The data was analyzed using variance, if it showed a significant effect, it was continued with the Duncan distance test. The results of this study found that placing frozen cement at different distances away from the liquid nitrogen surface reduced motility and survival percentage and did not affect abnormalities. Placing frozen semen from Bali cattle at a height of 15 cm or less from the surface of liquid nitrogen for 5 minutes did not reduce the quality of spermatozoa. Placing frozen Bali cattle semen as high as 20 cm or more above the surface of liquid nitrogen for 5 minutes reduces the quality of spermatozoa.